An experimental study on the effect of the flaring rate on flame dynamics in open pipes. (29th January 2022) - Dong, Jianfei; Deng, Haoxin; Xu, Zhuangzhuang; Yan, Mengmeng; Wei, Shengnan; Wang, Fahui; Wen, Xiaoping; Chen, Guoyan; Zhang, Anchao
Abstract: Under the condition that the gas composition constant equivalence ratio is Φ = 1, and the initial temperature and initial pressure are T 0 and P 0, respectively, the experimental study of the premixed gas flames with different hydrogen doping ratios ( φ = 10%–40%) is different. The behavior and shape change of propagation in the flaring rate pipe ( ƞ = 1.0–0.25). The study found that the pre-mixed gas flame in the flared pipe has undergone more complicated shape changes than other studies. One of the outstanding findings is that the tulip flame appeared twice in this open pipe experiment. And through the high-speed camera and high-frequency pressure sensor to obtain the tulip flame picture and the pressure change in the combustion chamber, comprehensive analysis of the experimental results, and the results show that every appearance of the tulip flame is accompanied by the deceleration of the flame front and the increase of overpressure in the combustion chamber. Highlights: An interesting phenomenon in which the tulip flame appears twice in a row was discovered. Independently designed solenoid valve control switch to ensure that the explosion vent opens or closes on time. In-depth analysis of the tulip flame from multiple angles.